Health Risk Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) and Heavy Metals In Grilled Chicken Meats From Benin, West Africa - EDIKOU, Koba Ulrich Spéro; DABADE, DELEY SYLVAIN; ATCHOUKE, Laurent G. D.; DOSSOU, JOSEPH (My University, 2023)
Background and Objective: There is concern about the safety of food, especially grilled foods in Africa. This study aimed to assess Polycyclic Aromatic Hydrocarbons (PAH) and heavy metals content in grilled chicken meat and health risk for consumers in Benin. Material and methods: A total of 35 samples of grilled chicken meat were collected from Cotonou and Abomey-calavi following various grilling processes and devices. PAHs were analyzed by gas chromatography coupled with mass spectrometry. Heavy metals were analyzed by atomic absorption spectrophotometer and mercury by spectrophotometer coupled with VP100 hydride generator. Estimated Daily intake (EDI) and Hazard Quotient (HQ) were used to evaluate the risk of exposure to benzo(a)pyrene, lead and cadmium. Results: whole grilled chicken meat (2.761-4.062 µg kg-1) did not meet the maximum limit of 2 µgkg-1 for benzo(a)pyrene set by European Union except whole pre-cooked grilled chicken meat (0.333±0.033 µg kg-1) and whole grilled chicken meats with wood-device (1.493±0.055 µg kg-1). Regardless of the device, grilled chicken meat skewers contained a tolerable level of benzo(a)pyrene (1.216-1.892 µg kg-1). Lead level in whole (223.3±36 µg kg-1) and skewers (153.3±18 µgkg-1) chicken grilled on cabinet type charcoal-device exceeded the tolerated limit (100µg kg-1). However, levels of cadmium, mercury and arsenic were in accordance with the regulation in all analyzed samples. Only, HQ of benzo(a)pyrene was above 1 (Q > 1) for whole grilled chicken meats consumed daily. Regardless of consumption frequency, HQ of lead and cadmium were less than 1 ( HQ < 1) for all types of grilled chicken. Conclusion: No single metal poses health risk to consumers of grilled chicken meat in Benin. However, there is a potential risk associated with PAHs in the product, which should be managed.
Keywords: Benin; benzo(a)pyrene; benzo(b)fluoranthene; chicken meat; public health